Atroposelective Self‐Assembly of a Molecular Capsule from Amphiphilic Anthracene Trimers1. Issue 31 (19th June 2013) - Suzuki, Akira; Kondo, Kei; Akita, Munetaka; Yoshizawa, Michito
<x xml:space="preserve">Abstract</x> Atroposelective formation: Selective formation of a molecular capsule was demonstrated from an amphiphilic cis‐atropisomer bearing three anthracene rings and four sulfonate groups through hydrophobic and aromatic–aromatic interactions. The dimeric capsule binds small guest molecules; the resultant host–guest complexes exhibit ground‐state charge‐transfer interactions accompanied by changes in host emission.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>